Business Registration Reform Case Studies : Malaysia - Olaisen, John (World Bank, Washington, DC, 2017)
This collection of case studies describes experiences and draws lessons from varied business registration reform programs in economies in vastly different stages of development: Bulgaria, Estonia, Ireland, Madagascar, and Malaysia. Over the last twenty years, a number of countries have recognized the importance of smooth and efficient business start up procedures. A functioning business registration system is now viewed as an important regulatory requirement of any economy, and a predictable, transparent, and modern business registration system is acknowledged to help promote private sector growth and job generation. Business registration gives businesses formal status and formal operation in the marketplace. It is a dynamic process that impacts the life of its stakeholders, commercial counterparties, and employees by introducing new responsibilities, opportunities, and challenges.